Shabella Cake House / Jessica Debra Josephat ... [et al.] - Josephat, Jessica Debra; Adin, Sharon Rayner; Ghulabdin, Shaziella; Nurali, Nashroy Andryan; Mandarin, Khadijah (2010)
The name of our company is SHABELLA Cake House. Our mode of business is partnership. Since there are three of us, we have decided to nan1ed our company according to our names which is SHA for Sharon, BE for Jessica (her nick) and ELLA for Shaziella (her nick). Our two other partners, which is Nashroy and Khadijah was joining us while the name was created. So we have decided not to change the name so that it will be easier because we have used the name before Nashroy's and Khadijah's jointship.